1^2-2^2+3^2-4^2...+(-1)^n-1n^2=(-1)^n-1xn(n+1)⼀2数学归纳法

2025-02-24 05:34:10
推荐回答(1个)
回答1:

一、当n=1时,
  左边=1^2=1,
  右边=[(-1)^(1-1)]×1×(1+1)/2=1。
  等式成立。
二、当n=2时,
  左边=1^2-2^2=1-4=-3,
  右边=[(-1)^(2-1)]×2×(2+1)/2=-3。
  等式成立。
三、设当n=k时,等式成立,即:
  1^2-2^2+3^2+······+[(-1)^(k-1)]k^2=[(-1)^(k-1)]k(k+1)/2。
四、当n=k+1时,
  左边=1^2-2^2+3^2+······+[(-1)^(k-1)]k^2+[(-1)^k](k+1)^2
    =[(-1)^(k-1)]k(k+1)/2+[(-1)^k](k+1)^2
    ={[(-1)^k](k+1)/2}{[(-1)^(-1)]k+2(k+1)}
    ={[(-1)^k](k+1)/2}(-k+2k+2)
    ={[(-1)^k](k+1)/2}[(k+1)+1]
    =(-1)^[(k+1)-1](k+1)[(k+1)+1]/2,
  右边=(-1)^[(k+1)-1](k+1)[(k+1)+1]/2。
  等式成立。
∴当n为正整数时,有:
1^2-2^2+3^2+······+[(-1)^(n-1)]n^2=[(-1)^(n-1)]n(n+1)/2。